A Rare Case of Hemopericardium From a Ruptured Dissecting Pulmonary Artery Aneurysm: Postmortem Computed Tomography Scan and Autopsy Findings. (March 2018) - Tse, Rexson; Garland, Jack; Triggs, Yvonne; Stables, Simon
Abstract : Abstract: Nontraumatic hemopericardium is a potentially fatal pathology that is most commonly caused by myocardial wall rupture, ruptured aortic dissection, aortic aneurysm rupture, or a neoplastic process. A rare potential cause of hemopericardium is pulmonary artery dissection, with less than 100 reported cases in the literature. Pulmonary artery dissection is associated with pulmonary artery aneurysm, pulmonary artery hypertension, and congenital heart disease. We report a fatal case of nontraumatic hemopericardium caused by a ruptured dissecting pulmonary artery aneurysm in a 16-year-old girl with patent ductus arteriosus. The unenhanced postmortem computed tomography performed before autopsy was able to identify a large hemopericardium with a pulmonary artery aneurysm and lifting of mural calcification suggestive of a dissecting aneurysm. This enabled the pathologist to locate the exact rupture site that caused the hemopericardium.